Quaking - Erskine, Kathryn (Philomel Books, 2007)
Fourteen-year-old Matt, abused by her father, has spent years being shuffled around to relatives, and has worked hard to make herself invisible, but her life changes when she moves in with Sam and Jessica Fox, a Quaker couple who quickly make her feel safe, and who Matt feels compelled to stand up for when their anti-war sentiments and peace vigils come under attack in their Pennsylvania town.